Letter from Carl D. Duncan to Patricia Whiting, August 1, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan discusses his spiritual beliefs and future travel plans.